PHOTOMETRIC AND SPECTRAL RESEARCHES OF THE SEYFERT GALAXIES NGC 4151 AND NGC 7469 - Shomshekova, S.A.; Denissyuk, E.K.; Valiullin, R.R.; Kusakin, A.V.; Reva, I.V.; Krugov, M.A. (Academic Scientific Journal of Computer Science, 2020)
Seyfert galaxies are much closer than the rest intergalactic objects and therefore the study of them is the most suitable and it gives an information about the physical processes occurring in objects of this type. Spectra of the Seyfert 1 galaxies (Sy1) are represented by a set of forbidden and permitted emission lines. The latter ones consist of a narrow and a broad (up to 10000 km/s) components. The ionization source is an accretion disk. the energy of which is generated due to the accretion of the surrounding matter onto a central supermassive black hole. The region of formation of the broad hydrogen lines (BLR) consists of dense clouds of gas fibers and jets located near the gravitational center and rotating around it at high velocities. The sizes of BLR are about a few tenths of a parsec. The region of formation of narrow forbidden lines and narrow components of hydrogen lines (NLR) is more extended and farther from the center NLR has a lower density of gas. The extension of NLR in the galaxies is determined by the time delay (reverberation). As it turned out, they are from several light days to several light weeks and depend on the luminosity of the active nucleus of the Seyfert galaxy. This paper presents the results of photometric and spectral observations of Seyfert galaxies NGC4151 and NGC 7469. Observations were carried out with the 70-cm telescope AZT-8. Eastern and Western 1-meter telescopes of the Tien Shan Astronomical Observatory of the Fesenkov Astrophysical Institute. The estimations of brightness of NGC4151 (in the B V filters) and NGC7469 (in B V R filters) were obtained from 2013 to 2019. Based on the observational data. the light curves of the studied objects were made. Spectra of the galaxies were obtained in the absolute units. Variations of the level of continuum at two wavelengths λ=5100Å and 6300Å were studied.